The Mitochondrial Protein hFis1 Regulates Mitochondrial Fission in Mammalian Cells through an Interaction with the Dynamin-Like Protein DLP1 - Yoon, Yisang (American Society for Microbiology, 2003)
The yeast protein Fis1p has been shown to participate in mitochondrial fission mediated by the dynamin-related protein Dnm1p. In mammalian cells, the dynamin-like protein DLP1/Drp1 functions as a mitochondrial fission protein, but the mechanisms by which DLP1/Drp1 and the mitochondrial membrane interact during the fission process are undefined. In this study, we have tested the role of a mammalian homologue of Fis1p, hFis1, and provided new and mechanistic information about the control of mitochondrial fission in mammalian cells. Through differential tagging and deletion experiments, we demonstrate that the intact C-terminal structure of hFis1 is essential for mitochondrial localization, whereas the N-terminal region of hFis1 is necessary for mitochondrial fission. Remarkably, an increased level of cellular hFis1 strongly promotes mitochondrial fission, resulting in an accumulation of fragmented mitochondria. Conversely, cell microinjection of hFis1 antibodies or treatment with hFis1 antisense oligonucleotides induces an elongated and collapsed mitochondrial morphology. Further, fluorescence resonance energy transfer and coimmunoprecipitation studies demonstrate that hFis1 interacts with DLP1. These results suggest that hFis1 participates in mitochondrial fission through an interaction that recruits DLP1 from the cytosol. We propose that hFis1 is a limiting factor in mitochondrial fission and that the number of hFis1 molecules on the mitochondrial surface determines fission frequency.